Vestibular neuronitis after COVID-19 vaccination. Issue 6 (6th June 2022) - Bramer, Solange; Jaffe, Yvette; Sivagnanaratnam, Aravinth
Abstract : A woman in her 50s presented with acute vertigo and vomiting within 72 hours of receiving the Pfizer-BioNTech COVID-19 vaccine. The only neurological deficit was an impaired vestibulo-ocular reflex with horizontal nystagmus. The patient was subsequently diagnosed with vestibular neuronitis. She was managed symptomatically with prochlorperazine and betahistine, and underwent vestibular rehabilitation for 6 weeks. She made a full recovery and experienced no further symptoms. She received the second dose of the vaccine without complications. This case demonstrates a temporal association between COVID-19 vaccination and vestibular neuronitis. Neurological adverse events are rare but recognised side effects of COVID-19 vaccines and healthcare professionals should be aware of them. This ensures timely management of patients with such presentations. Treatment should be the same as for non-vaccine-associated vestibular neuronitis. The nature of the relationship between COVID-19 vaccination and vestibular neuronitis remains unclear and patients therefore require investigations to exclude other recognised causes of vestibular neuronitis.